Proposta de uma ontologia como modelo de referência no domínio da memória organizacional histórica - Estevão, Janete Saldanha Bach (2012)
The Historical Organizational Memory consists of the main documents that register the trajectory of an institution. It represents the legacy of this organization, available to its stakeholders in a structured and dynamic way. The ontologies aim to make sense of the content of these repositories, using the semantic relationship of the terms that can represent the area. This work establishes the basis for proposing an ontology that serves as a reference model in the Historical Memory Organization field, promoting accurate responses from search engines and information retrieval. The universe of this research is represented by companies participating in the Permanent Forum on Knowledge Management, Communication and Memory of the Brazilian Association of Business Communication (ABERJE), which already have initiatives in Historical Organizational Memory (HOM). It identifies, among other things, whether companies use a standardized instrument of information representation, such as controlled vocabularies, taxonomies and thesauri. As a method for identification of these potential instruments adopted by the institutions used in this study, we used the exploratory research, interviews with data collection, followed by content analysis and description of the results. It is intended that this ontology will serve as a reference model for Historical Organizational Memory projects, which can be extended by domain experts from the declared and interrelated concepts in this proposal: types of documents, collections, subjects covered by the items, the target audience and information dissemination channels. This ontology also provides subsidies to promote the understanding of key concepts of the domain in question and greater accuracy in the recovery of institutional holdings information. From these concepts it was possible to explain the relationship between the physical composition of a HOM's collection, whether they are individual items or part of a collection, what subject they talk about, to whom it is intended and what channels of information dissemination are delivered. From a potential need for standardization of the descriptive representation of documents and content repositories, it is expected to contribute with the information retrieved as a result that is relevant in the searching context, providing the repositories the possibility of usage of an ontological structure in the Historical Organizational Memory field.